Analisis Kesalahan Berbahasa Tataran Semantik dalam Teks Deskripsi Siswa Kelas V A di SD 1 Sidorekso - Noor Faizul Muna; Ika Cintiya Claudia Bella; Amelia Rahmawati; Rani Setiawaty (FKIP Universitas Khairun, 2025)
This study aims to analyze the forms of semantic errors contained in the descriptive text essays of grade V A students at SD 1 Sidorekso. The subjects of this research are students of class V A at SD 1 Sidorekso. The object of this research is semantic language errors in the description text essays of grade V A students at SD 1 Sidorekso. The research method used is descriptive qualitative. The data collection technique is done by documentation, using reading techniques and note-taking techniques. The data analysis method used is pairing by using techniques in the form of referential and again by using the replaced technique. The data analysis technique used is the Miles & Huberman analysis technique, namely, data collection, data reduction, data presentation/display, and verification/conclusion drawing. The results showed that there were semantic errors in the description texts of grade V A students at SD 1 Sidorekso, which included ambiguity, pleonasm, diction, and hypercorrection.